Vertical distribution and major influencing factors of soil selenium in tropical climate: A case study of Chengmai County, Hainan Island. (January 2023) - Gong, Jingjing; Gao, Jianweng; Fu, Yangang; Tang, Shixin; Cai, Yongwen; Yang, Jianzhou; Wu, Hui; Ma, Shengming
Abstract: Soil selenium is of great significance to human health. Soil-forming parent rocks are the most critical factor that influences soil Se levels. Chengmai County, Hainan Island, has a tropical climate and diverse types of parent rocks, in which soil Se content is high. This study investigated the vertical distribution of soil Se from various parent rock substrates under tropical climatic conditions, and the factors that influence these soil Se contents, with 69 vertical soil profiles covering Chengmai County. The vertical distribution of soil Se and correlations with CIA (chemical alteration index), Al2 O3, TFe2 O3 (total iron oxide expressed as Fe2 O3 ), total iodine, SOC (soil organic carbon), and pH were analysed. As per the results, the mean ± standard error of Se content in the A, B, and C horizons was 0.88 ± 0.13 mg/kg, 0.77 ± 0.08 mg/kg and 0.45 ± 0.05 mg/kg, respectively. The parent rock strictly controlled the horizon distribution of Se in the A-horizon. Soil Se showed A-B-horizons-enrichment in the vertical profile, especially in soil profiles overlying granite and basalt. It is hypothesised that the Se enriched in soils developed from the Tuolie Formation due to the release of Se from the weathering process of Se-rich rocks. Meanwhile, Se in soils developed from granite and basalt is more closely associated with exogenous input. Another crucial factor for the high level of Se in Chengmai County is the tropical climate, which has led the rocks to generally undergo intense chemical weathering. This results in soils rich in clay minerals and Fe/Al oxyhydroxides, which easily absorb and retain Se. Furthermore, the Se content of the B-horizon was generally higher than that of the A-horizon due to leaching. These results provide further knowledge and understanding of the geochemical behaviour of soil Se and guide the evaluation of Se-rich land resources under tropical climatic conditions. Graphical abstract: Image 1 Highlights: Soil Se levels were high in the A, B, and C horizons in Chengmai County, Hainan Island. Soil Se showed A-B-horizons-enrichment in the vertical profile. The tropical climate is a crucial factor for the high soil Se content. The distribution of Se content below the B horizon was most closely related to OM.